2008
DOI: 10.1007/s10681-008-9678-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of a Brassica carinata inbred line incorporating genes for low glucosinolate content from B. juncea

Abstract: The presence of high levels of sinigrin in the seeds represents a serious constraint for the commercial utilisation of Ethiopian mustard (Brassica carinata A. Braun) meal. The objective of this research was the introgression of genes for low glucosinolate content from B. juncea into B. carinata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 29 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…These authors postulated that genotypes containing mainly sinigrin showed a larger flowering cycle. Sinigrin is the main glucosinolate in Ethiopian mustard seeds and leaves [25]. Although it is difficult to state with precision the degree of participation of the major cell constituents of leaves (protein, lipids, starch, cellulose, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…These authors postulated that genotypes containing mainly sinigrin showed a larger flowering cycle. Sinigrin is the main glucosinolate in Ethiopian mustard seeds and leaves [25]. Although it is difficult to state with precision the degree of participation of the major cell constituents of leaves (protein, lipids, starch, cellulose, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Serendipitously, in the Brassica genus, several crop species have genomes in common and the ability to perform interspecific hybridizations allows for the transfer of useful adaptive traits between species for targeted crop improvement through conventional breeding (Katche et al 2019). Interspecific crosses with the compatible allotetraploid species B. napus and B. juncea have resulted in B. carinata lines with decreased glucosinolate content (Márquez-Lema et al 2008) and increased seed oil content (Sheikh et al 2009), as well as increased overall genetic diversity (Sheikh et al 2011). Similarly, C22:1 levels in B. carinata were significantly reduced through crosses to both B. napus (Fernandez-Escobar et al 1988) and B. juncea (Getinet et al 1994).…”
Section: Introductionmentioning
confidence: 99%